This is what we experienced during teaching performance in a Microteaching course: An emotional geography - Mujab, Bangkit Saiful; Puspitasari, Dewi; Rahmah, Rayinda Eva (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2023)
This research presented the narration of students’ emotions when microteaching practice. By using the narrative inquiry method, this research showed students’ emotions when they faced the challenges in teaching English performance in the microteaching course. Based on the five students' reflections, we took the data and then analyzed them using the thematic analysis method. The result of the research was related to emotional geography theory by Andy Hargreaves. Based on the analysis result, the researchers found that participants experienced the positive and negative emotions. In positive emotions, it happened when the participants did not nervous during perform in front of the classroom, did not feel nervous when taught different age and gender, felt comfortable and easier that caused by respect, felt so proud that caused by the appreciation, did not have the difficulty in delivering the materials, and felt enthusiastic when got the lecture advices. To negative emotions, it happened when the participants felt so nervous because the lecture and friends were very near, felt so nervous because it was the first time to practice teaching in front of the classroom, felt difficult in teaching because there was no learning tool to support, felt insecure with lecturer advices, and felt difficult when the lecturer instructed to use English in teaching practice.